Prevalence of HPV 16/18 positivity and cytological findings in the post-vaccination era: a retrospective study at SASMEC@IIUM - Ahmad Affandi, Khairunisa; Hamdan, Asmah Hanim; Abd. Fuaat, Azliana; A. Talib, Noorlelawati; Abdul Halim, Sarah (College of Pathologists, Academy of Medicine Malaysia, 2025)
Introduction: Malaysia’s national HPV vaccination program was introduced over a decade ago to reduce cervical cancer rates. As vaccinated cohorts enter screening age, evaluating the local prevalence of HPV 16/18 is essential to assess vaccine impact and guide screening practices. Cytology remains central to cervical screening, but may not detect all high-risk infections. This study aims to determine the prevalence of HPV 16/18 among HPV-positive women at SASMEC@IIUM and examine their correlation with cytological findings. Materials and Methods: A retrospective cross-sectional review of medical records was conducted for 304 HPV-positive women screened between 2019 and 2024. Data extracted included age, HPV genotype, and Pap smear results. Cases positive for HPV 16 and/or 18 were categorised using the Bethesda System. Results: The median age was 35 years (range: 19-64). HPV 16 and/or 18 were detected in 51 cases (16.8%): 17 (5.6%) with HPV 16 alone, 19 (6.3%) with HPV 18 alone, and 15 (4.9%) with both. Among these, 26 (51%) had negative cytology, while 17 (33.3%) showed epithelial abnormalities, indicating genotype–cytology discordance. Discussion and Conclusion: HPV 16/18 remains detectable in the post-vaccination era, with over half of positive cases showing negative cytology. These findings support the incorporation of HPV genotyping into routine screening and highlight the need for continued local monitoring.